Fraudulent and Questionable Financial Reporting: A Corporate Perspective (Book). - Albrecht, W. Steve (The Accounting Review, 1988)
Abstract Reviews the book "Fraudulent and Questionable Financial Reporting: A Corporate Perspective," by Kenneth A. Merchant.